PENGARUH KOMPENSASI, KOMPETENSI, MOTIVASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT DI BEKASI - PRICILLA DONNA PAULINE SETIO; Yupiter Gulo (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
This study aims to determine the effect of compensation, competence and motivation on employee performance at Hospital. The rapid growth of hospitals and not limited by geography makes competition for health services more complex and employee performance declines related to compensation, inappropriate competencies and low employee motivation. The population and sample are 100 employees. Using Likert scale measurement, data were collected using a questionnaire. The analysis technique used multiple linear regression in testing the research model and hypotheses. The results showed that compensation and motivation had no significant effect, while competence had a significant effect on employee performance. Therefore, hospital managers must pay serious attention to improving the competence of their employees.